Sarrasine di Balzac, S/Z di Barthes e il mito di Ermafrodito - Mario Gennari (Firenze University Press, 2022)
The article focuses on Honoré de Balzac's Sarrasine and Zambinella figures, considered in their relation through the analysis of Roland Barthes. Examined in the context of social inhuman practices between XVI and XIX centuries, the two enigmatic characters are interpreted on their recall to the connotative aspects traced back to male and female dimensions of human being and on the meaning evoked by the myth of Ermafrodito. Thinking the different codes of existence forms concerns a pedagogical perspective that suggests an education steered towards a personal awareness and a free expression of the denotative inner mystery of human being and its nature.